2016
DOI: 10.4081/jlimnol.2016.1366
|View full text |Cite
|
Sign up to set email alerts
|

The diet of introduced brook trout (Salvelinus fontinalis; Mitchill, 1814) in an alpine area and a literature review on its feeding ecology

Abstract: <p>Introduced fish are a major threat for high altitude aquatic habitats and <em>Salvelinus fontinalis</em> have been widely used throughout the Alps for stocking lakes and rivers. Understanding its feeding ecology is a basic, but essential tool for interpreting its impact. To assess which factors determine the diet of <em>S. fontinalis</em> we analyzed more than 500 stomachs from several introduced populations from the Gran Paradiso National Park (GPNP, Western Italian Alps) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…These inferences indicated that littoral invertebrates, mostly dominated by chironomids, would be mainly exposed to salmonid predation in the lake and are consistent with empirical diet analyses conducted in mountain lakes, identifying chironomids as a primary resource for stocked salmonids (Cavalli 1997 ; Tiberti et al. 2016 ; Mouillet et al. 2018 ).…”
Section: Discussionsupporting
confidence: 69%
“…These inferences indicated that littoral invertebrates, mostly dominated by chironomids, would be mainly exposed to salmonid predation in the lake and are consistent with empirical diet analyses conducted in mountain lakes, identifying chironomids as a primary resource for stocked salmonids (Cavalli 1997 ; Tiberti et al. 2016 ; Mouillet et al. 2018 ).…”
Section: Discussionsupporting
confidence: 69%
“…Experimental studies on Brook Trout suggest that their growth rate is reduced above 16°C (Chadwick & McCormick, 2017) but under high food rations salmonids may overcome the temperature‐induced limitation (McCullough, Spalding, Sturdevant, & Hicks, 2001; Richter & Kolmes, 2005; Thompson & Beauchamp, 2016). Conditions in Castle Lake's littoral habitat during early ice break‐up years should have resulted in high growth rates of Brook Trout, if they foraged opportunistically on the most abundant resource (Tiberti et al, 2016). Our telemetry and isotopic data show that Brook Trout did not utilize littoral habitat, rather they selected for preferable thermal conditions with a relatively lower abundance of pelagic prey.…”
Section: Discussionmentioning
confidence: 99%
“…Our telemetry and isotopic data show that Brook Trout did not utilize littoral habitat, rather they selected for preferable thermal conditions with a relatively lower abundance of pelagic prey. Interestingly, Tiberti et al (2016) also show that zooplankton were rarely observed in Brook Trout diets which suggests it is less energetically efficient and could lead to reduced fitness. Reductions in body size and fecundity have been associated with climate change across both terrestrial, freshwater and marine systems (Baudron, Needle, Rijnsdorp, & Tara Marshall, 2014; Sheridan & Bickford, 2011), for plants, animals and fish (Farmer, Marschall, Dabrowski, & Ludsin, 2015; Walther et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An undetermined fraction of the reproductive newt population was therefore loss through direct predation. The impact of fish introduction is usually ascribed to predation on larval stages (Brönmark & Edenhamn, ; Remon, Bower, Gaston, Clulow, & Mahony, ; Tiberti & von Hardenberg, ), but there is various evidence describing the ability of adult salmonids – most commonly used to stock mountain lakes – to ingest large prey items, including adult amphibians (Denoël et al, ; Tiberti et al, ). The possibility for fish to feed on adult amphibians is linked to the size ratio between predator and prey: in P1, S. trutta can achieve remarkable sizes (> 400 mm), which allow it to feed on relatively large prey items (e.g.…”
Section: Discussionmentioning
confidence: 99%